2018
DOI: 10.1007/s00125-018-4786-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of type 1 diabetes with teplizumab: clinical and immunological follow-up after 7 years from diagnosis

Abstract: Aims/hypothesis The long-term effects of successful immune therapies for treatment of type 1 diabetes have not been well studied. The Autoimmunity-Blocking Antibody for Tolerance (AbATE) trial evaluated teplizumab, an Fc receptor non-binding humanised anti-CD3 monoclonal antibody in individuals with new-onset type 1 diabetes, and ended in 2011. Clinical drugtreated responders showed an increased frequency of 'partially exhausted' CD8 + T cells. We studied the clinical, immunological and metabolic status of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
66
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 18 publications
0
66
0
6
Order By: Relevance
“…The TrialNet group has recruited 76 children to a placebo-controlled study designed to test the ability of teplizumab to delay onset of insulin therapy in at-risk individuals presenting with at least two autoantibodies and an abnormal OGTT but no hyperglycaemia. Importantly, it would not have been possible to allow such a large number of patients to have undergone this therapy had it not been for the favourable safety profile of teplizumab, a major feature that is confirmed by the results of the 7 year follow-up study described here [27].…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…The TrialNet group has recruited 76 children to a placebo-controlled study designed to test the ability of teplizumab to delay onset of insulin therapy in at-risk individuals presenting with at least two autoantibodies and an abnormal OGTT but no hyperglycaemia. Importantly, it would not have been possible to allow such a large number of patients to have undergone this therapy had it not been for the favourable safety profile of teplizumab, a major feature that is confirmed by the results of the 7 year follow-up study described here [27].…”
mentioning
confidence: 75%
“…<7.5% difference between the two values, as used previously in some clinical studies. The authors found that, overall, C-peptide levels were not significantly different between drug-treated patients and control participants during the MMTT; however, C-peptide levels were higher in drug-treated responders (identified at 1 year) than in control participants and drug-treated non-responders [27]. The question of the real clinical meaning of this difference in C-peptide is important given that it was not associated with better glycaemic control or a decrease in insulin requirements.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In conclusion, circulating plasma-borne miR-409-3p may represent a candidate biomarker of islet inflammation in both type 1 diabetic mice and humans and could be potentially useful for serial tracking of islet inflammation or response to immune therapies, such as teplizumab aCD3 therapy, in intervention and prevention trials [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Teplizumab (mAbs against CD3 with mutated Fc-chain) has recently been shown to slow down progression of T1D in high-risk groups. [97][98][99][100][101][102] The long-term effects were due to Teff depletion and enhanced Treg activity. The drug is now in phase 3 trials for T1D in the PROTECT study (NCT03875729; https://www.type1 diabe tesre search.org.uk/curre nt-trial s/ prote ct-study/).…”
Section: Immune Therapy: Target Cell-specific Immune Pathways Involmentioning
confidence: 99%